Förskolepersonals tal om ansvar i relation till den förtydligade ansvarsstrukturen i svensk förskolepolicy - Anita Eriksson; Ann-Katrin Svensson; Dennis Beach (Educare)
Based on interviews, field conversations and participant observation with head teachers and preschool teachers at four preschools in four different municipalities in Sweden, this article considers how preschool staff interpret and describe their workplace responsibilities four years after the revision of these in the 2010 Education Act and the preschool curriculum and how these descriptions may reflect increasing professionalization.The results demonstratethat the national curriculum discourse of increased preschool teacher professional responsibility was reproduced in general talk about work-duties and responsibilities, but that in more specific conversation related to concrete examples and tasks this was not as clearly the case. Instead, there was a re-contextualisation of the prevailing conditions in the actual preschool contexts. There was also a distinction between the two groups of participants. The head teachers expressed high expectations for preschool teachers to be responsible leaders in the pedagogical activities carried out by the team, but the preschool teachers did not represent themselves as leaders in the same sense. Finally, this study addresses whether the way of talking about the preschool teachers’ responsibilities can contribute to or limit their professionalisation.